2022
DOI: 10.1002/joc.7695
|View full text |Cite
|
Sign up to set email alerts
|

Understanding summer wind systems over the eastern Mediterranean in a high‐resolution climate simulation

Abstract: Regional and local wind systems are often complex, particularly near coastal areas with a highly variable orography. Thus, the realistic representation of regional wind systems in weather and climate models is of strong relevance. Here, we evaluate the ability of a 13‐year convection‐permitting climate simulation in reproducing the interaction of several regional summer wind systems over the complex orography in the eastern Mediterranean region. The COSMO‐CLM simulations are driven by hourly ERA‐5 reanalysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 66 publications
(119 reference statements)
0
0
0
Order By: Relevance
“…They found that the high-resolution model significantly improved the forecasting of extreme weather events. Latt et al [5] found that the high-resolution COSMO-CLM (Continuous Consortium for Scale Modeling in Climate Mode) model simulation portrayed the main characteristics of regional winds, with the regional climate numerical model per-forming better in regions with complex topography. For certain extreme weather conditions and regions with complex terrain, higher model resolution leads to some improvement in simulation results.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the high-resolution model significantly improved the forecasting of extreme weather events. Latt et al [5] found that the high-resolution COSMO-CLM (Continuous Consortium for Scale Modeling in Climate Mode) model simulation portrayed the main characteristics of regional winds, with the regional climate numerical model per-forming better in regions with complex topography. For certain extreme weather conditions and regions with complex terrain, higher model resolution leads to some improvement in simulation results.…”
Section: Introductionmentioning
confidence: 99%
“…The Middle East, renowned for its hot and arid summer climate, offers a dynamic setting for wind projections influenced by numerous climatic factors (Ziv et al, 2004;Harpaz et al, 2014;Hochman et al, 2021). The region's summer months are marked by high temperatures and dry landscapes, creating a complex interaction of atmospheric dynamics that significantly influence wind patterns (Hochman et al, 2022;Latt et al, 2022). Key regional weather systems, such as the subtropical high and the Persian Trough, play a crucial role in shaping these prevailing winds (Alpert et al, 2004a,b;Hochman et al, 2018b,c;Alpert et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the region's summer climate is characterized by frequent dust storms, further complicating wind dynamics (Rezazadeh et al, 2013;Crouvi et al, 2017;Baltaci, 2021;Gasch et al, 2017). Strong diurnal temperature variations and the development of thermal low-pressure systems contribute to localized wind patterns, such as sea breezes and mountain-valley winds (Kunin et al, 2019;Latt et al, 2022;El-Geziry et al, 2021). Integrating these climatic details into high-resolution models is essential for maximizing the region's wind energy potential (Latt et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations